Factors associated with the Success or Failure of Artificial Intrauterine Insemination among Infertile Iraqi Women-Clinical Evaluation and Outcome - Al-Nedaw, Israa Abdulnabi (Academic Journal of Clinicians, 2025)
Intrauterine artificial insemination (IUI) is considered the first option among other modalities for treatment of infertility because it is low invasive and less traumatic in addition to lower costs. However, IUI is still not assured method of pregnancy. Furthermore, several factors may contribute to success or failure of IUI procedures, such as patient’s age, oocyte quality, sperm’s parameter and reproductive health all can affect the success of IUI. In Iraq, few studies have conducted to assess the outcomes of IUI and the factors that may affect the success or failure of this procedure, hence we conducted this study aiming to fill part of the gap in this topic. In this prospective observational study, we aimed to assess the successful pregnancy rate after the IUI and the factors that contribute to success or failure of the procedure among group of Iraqi patients in Al-Najaf fertility center, during a period of 26 months from April 2022 to July 2024 the studied group was made up of 116 women who underwent artificial intrauterine insemination. Our findings and revealed a pregnancy successful rate of 20.7% and several factors showed significant association with good IUI outcome and higher pregnancy rate and these factors were younger age women (<35 years), duration of infertility < 3 years, multi-follicular response, total motile sperm count (TMSC) ≥10 million, combined ovarian stimulation, thick endometrium and normal BMI. Our findings were comparable to previous literatures in Iraq and other countries. The success rate of IUI had a wide range of variation worldwide. Further studies are highly suggested for more precise conclusions and recommendations.